Deltamethrin Microencapsulation in Emulsion Paint Binder and Its Long-Term Efficacy Against Dengue Vector Aedes aegypti - Acharya, B. N.; Ahirwar, Rajkumar; Dhiman, Sunil; Yadav, Kavita; Pandey, Pratibha; Sukumaran, Devanathan (Frontiers in Public Health, 2021)
Various control interventions have been effective in the control of arthropod vectors to certain extent; still sustained vector control is an outstanding problem globally. Insecticide based formulations have been found to be useful, however the proper delivery of active molecules to target vectors is important. Currently, synthetic pyrethroid deltamethrin (DM) has been microencapsulated in the emulsion paint binder and evaluated for long-term effectiveness against dengue vector Aedes aegypti. Different composition of emulsion binder were prepared by varying the content of monomer and DM. Selection was made for the composition yielding the best combination of properties like solid content, intrinsic viscosity and DM content. Developed formulation was tested against laboratory reared and pathogen free Ae. aegypti mosquitoes. Encapsulation of DM in emulsion binder during polymerization showed uniform distribution. The optimized formulation was stable and doesn’t have considerable plasticizing effect. Scanning electron microscopy revealed that grain like micro crystals of DM and surfactant sodium lauryl sulfate (SDS) were uniformly distributed on the formulation surface. The best optimized formulation was highly effective against dengue vector Ae. aegypti and found to provided efficacy upto 18 months of application. The knockdown time (KDT) values KDT10 and KDT50 were 7.4 min (95% CI: 5.6-9.1) and 22.1 min (95% CI: 19.7-24.3) respectively, whereas 24hr corrected mortality was 90% (95% CI: 82.5-97.5) after 18 months of application (T18). The probit model used to determine knockdown values did not deviate from the linearity and displayed normal distribution of knockdown % with time for different formulations (p≥0.1). Presently developed DM microencapsulated emulsion binder was stable, smooth and uniform. The binder displayed excellent anti-insect property and was capable of providing long-term effectiveness against dengue vectors Ae. aegypti. Such formulation after field scale evaluation could be very useful in attaining long term protection from arthropod vectors.